Capital Structure and Profitability of LQ45 Index in Indonesia : Pecking Order Theory Approach - Evelyn Wijaya; Nur Fadjrih Asyik; Fadrul Fadrul (Journal of Applied Business and Technology, 2020)
Capital structure and profitability are part of company's financial system. Capital structure leads to company funding by utilizing long-term debt, preferred stock, and shareholder capital, while profitability refers to company's ability to generate profits. This study aims to analyze the effect of tangibility, growth, and company size on capital structure and profitability on LQ45 index. Sampling was carried out by purposive sampling technique and obtained 38 companies. Smart PLS program was utilized to assist research data analysis process. Results indicated that reliability, growth and company size had a significant effect on capital structure but they did not have a significant effect on profitability. Additionally, capital structure had a significant negative effect on profitability. The research results support pecking order theory which believes that the lower the company's debt, the higher the company's profitability.